Effect of soapwort extract as an alternative to albumin on the physical, textural, sensory, and rheological properties of marshmallow - Ozcan, Yilmaz; Icyer, Necattin Cihat; Ozmen, Duygu; Toker, Omer Said (WILEY, 2022)
Marshmallow is foam-like confectionery product. Albumin is a protein of animal origin, which is used in the production of marshmallow and is generally used for stabilizing and foaming purposes, with various disadvantages such as limited pH and ionic strength diversity. The objective of this study was to take the advantage of foam-forming ability of soapwort extract in the production of marshmallow. For this purpose, soapwort extract was added to the formulations with soapwort(s):albumin (a) ratios of 100:0, 75:25, 50:50, 25:75, and 0:100. Density, overrun, texture, rheological, and sensory properties were examined using mixture design to establish model for the quality parameters mention with respect to albumin and soap extract concentration. Density, overrun, color, and some sensory properties (springiness, overall acceptance) revealed significant difference (p < .10). Considering the sensory properties, the use of s25/a75 ratios can be suggested as an alternative that improves product properties in marshmallow production. Novelty impact statement As an alternative to albumin, which is used for stabilization and foaming and has various disadvantages such as limited pH and ionic strength variety, soapwort extract can provide significant improvements.
Keywords: HYDROCOLLOIDS; EMULSIFIERS; STABILITY; Food Science & Technology